Modeling of Pretreatment and Combined Alkaline and Enzymatic Hydrolyses of Blue Agave Bagasse in Corotating Twin‐Screw Extruders. Issue 3 (29th March 2022) - Morales‐Huerta, Juan Carlos; Hernández‐Meléndez, Oscar; Garcés‐Sandoval, Fernando Iván; Montiel, Carmina; Hernández‐Luna, Martín Guillermo; Manero, Octavio; Bárzana, Eduardo; Vivaldo‐Lima, Eduardo
Abstract: A recently developed model for pretreatment and acid or alkaline hydrolyses of lignocellulosic biomasses, including blue agave bagasse (BAB), in twin‐screw corotating extruders is extended to the case where enzymes are incorporated into the formulation. The model describes the deconstruction and degradation of BAB, as well as the production of simple sugars at the end of the extrusion process. Experiments using NaOH for delignification and alkaline hydrolysis of BAB, H3 PO4 for neutralization, and different enzymatic cocktails for bioextrusion are reported. The effects of temperature, NaOH concentration, enzymatic cocktail used and its concentration, residence time, and configuration of screw elements on degree of degradation and production of sugars are assessed. It turned out that temperature, NaOH concentration, and enzymatic cocktails are the key factors in the extraction and hydrolysis of hemicellulose (H) and cellulose (C) to produce glucose (G). Good agreement between experimental data and model predictions is observed. Abstract : A combined experimental‐modeling study on the pretreatment and alkaline/enzymatic hydrolyses of blue agave bagasse in twin‐screw extruders is presented. The extruder has a modular screw configuration with different elements. Alkaline and enzymatic hydrolyses are modeled assuming that the extruder behaves as a series of continuously stirred tank reactors. Good agreement between calculated profiles and experimental data is obtained.